PENGARUH PENGGUNAAN KATALISATOR BROQUET DAN ECO RACING TERHADAP PERFORMA MESIN SEPEDA MOTOR 4 LANGKAH 110 CC - Zaen W.H., M. Bagus; Hadromi, Hadromi (Automotive Science and Education Journal, 2021)
There are many ways that can be done to reduce the problem of fuel scarcity due to the increasing number of motorcycle usage, one of which is to make engine performance more efficient by adding catalysts and additives to the fuel used. Broquet is a catalyst product and Eco Racing is a fuel additive product that works to improve the combustion reaction process and its quality. This study aims to determine the effect of using Broquet and Eco Racing on engine performance including torque and power on a pertalite 4-stroke engine type motor and to determine the effectiveness of the product in improving engine performance. This research is using experimental method. Torque and power at the beginning of 4500 rpm engine speed testing with Broquet and Eco Racing has increased and then at the next engine speed gradually decreases. The use of Broquet and Eco Racing in pertalite influences engine performance and the use of Broquet has more effectiveness in improving engine performance at the start of engine rotation compared to Eco Racing. Keywords: Broquet, Eco Racing, Motorcycle engine performance.